Partilha administrativa do sensível: entre fatos, provas e prognoses administrativas - Lucena, Pedro Flávio Cardoso (2020)
This research aims to investigate the need and possible existence of a theoretical proposal capable of justifying a particular rationalization mode for the processing of administrative facts, proof and administrative prognosis in administrative process. The following hypothesis is formulated: if the brazilian legal system, strictly speaking, requires a format specific to the handling of administrative processes, then the Science of Law will be responsible for examining and proposing a rational theoretical construction aimed at the composition of this activity. Illustratively, we cite the Federal Constitution of 1988, which in numerous clauses explains the distinction of procedural types – legislative, administrative and judicial. In addition, several infraconstitutional laws highlight singularities in the types of proceedings under brazilian law – such as Federal Law nº 9.784/99. Therefore, if there are normative determinations, then there must be a theoretical justification capable of rationalizing the processing of administrative facts. In this light, the research is justified in view of the fact that confusions in understanding the administrative functional dynamics, as a rule, give rise to practical problems not only for Public Administration, but also for the exercise of other state competences: not by coincidence, the State stands out as a of the largest judicial litigants in Brazil. Another indication comes down to the fact that, after more than 30 years of constitutional validity, the brazilian legal system continues to incorporate laws to govern elementary actions in Public Law – as in the case of Law nº 13.655/2018. In view of the above, and especially in view of the existence of the aforementioned normative manifestations, the study proposes the following thesis: there is a rationalization proper to the administrative process, since the state action, in such cases, is guided by a phenomenon called administrative partition of the sensitive. This is characterized in the following terms: in view of the preponderant performance of Public Administration on a material plane, it partitions – participate – with the administrators the existing factual reality and, at the same time, partitions – it has for itself, exclusively – a constitutional competence decision-making. The practical application of the proposed theory is evidenced in administrative processes, since in them the State has the competence to be a party, as well as the competence to judge. The observed phenomenon indicates the need for a form of reasoning in relation to the administrative functional exercise, which ends up resulting in a unique way of fixing legal facts, examining proof and deciding administrative prognoses in administrative processes. As for the processing of the legal fact, we propose a tripartite dynamic, that is, the lato sensu fixation of the legal facts, the stricto sensu administrative fixation of the legal facts and the stricto sensu normative fixation of the relevant legal facts. Regarding the proof, we identified that its processing takes place, primarily, within the scope of the stricto sensu normative fixation of the relevant legal facts – through a parameterization determined by the legal system itself. Finally, in view of the administrative prognoses, we verify that they are conditioned to each of the dynamics previously listed, whose conclusion can be attested, for example, by examining the topic of risk management in Public Administration